Evidence on Productivity, Comparative Advantage, and Networks in the Export Performance of Firms - Ricci, Luca.; Trionfetti, Federico (Washington, D.C. : International Monetary Fund, 2011)
This paper tests the effect of comparative advantage, size, and networking on the firm probability of exporting. The closest theoretical framework is the one of Bernard, Redding, and Schott (2007), with firm heterogeneity across countries and industries. We use a recently assembled multi-country multi-industry firm level dataset, and construct original measures of comparative advantage. The results show that firms are more likely to export if they belong to the comparative advantage industry, if they enjoy a higher productivity, or if they benefit from foreign, domestic, or communication networks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet